2021
DOI: 10.1155/2021/6661763
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Self-Made Polyurethane-Covered Stent Implantation for the Treatment of Coronary Artery Perforations

Abstract: Objectives. The present study aimed to investigate the short- and long-term clinical outcomes of self-made polyurethane-covered stents (PU-CS) in patients for the management of coronary artery perforation (CAP) during percutaneous coronary intervention (PCI). Background. Coronary artery perforation is reckoned as a serious complication in PCI and associated with considerable morbidity and mortality. Covered stents have been used for treating the life-threatening CAP during PCI. But in some catheterization labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The recuperation duration following the procedure was not extended, and the patient was discharged without any complications on the 2nd day after the surgery. 19 Song et al 19 compared the clinical outcomes of self-made polyurethane-covered stent (PU-CS) implantation to treat CAP and found that the self-assembled PU-CS exhibited impressive efficacy in achieving successful delivery and sealing of critical CAP during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The recuperation duration following the procedure was not extended, and the patient was discharged without any complications on the 2nd day after the surgery. 19 Song et al 19 compared the clinical outcomes of self-made polyurethane-covered stent (PU-CS) implantation to treat CAP and found that the self-assembled PU-CS exhibited impressive efficacy in achieving successful delivery and sealing of critical CAP during PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary calcification, tortuosity, and poor preparation of the vessel before stent deployment are the major reasons leading to stent loss. [24] Stent loss occurred in 1.3% of PCIs in a meta-analysis of 71,665 PCIs. Recent studies report that an incidence of 0.3%.…”
Section: Covered Stents Available [Figure 6a-c]mentioning
confidence: 99%
“…Aneu GraftDX is a 316L stainless steel stent covered with equine pericardium, which can be successfully employed in CAP. [15] However, covered stents are not universally available in all catheterization laboratories. Some self-made covered stents can also be developed as a bail-out strategy.…”
Section: Large Cap Covered Stentsmentioning
confidence: 99%